EFFECTS OF DHIKR ON SPIRITUALITY AND CORTISOL LEVELS AMONG PATIENTS WITH HEART FAILURE: A PILOT STUDY - Okviasanti, Fanni; Putra, Suhartono Taat; Bakar, Abu; yusuf, Ah (Journal of Vocational Nursing, 2023)
Introduction: Depression and anxiety are common comorbid conditions in patients with heart failure (HF). Spirituality was found to have a positive impact on patients' mental health status. However, whether the spiritual practice affects physiological modulation is still questionable. Therefore, this study aimed to analyze the effect of dhikr as spiritual practice on spirituality and cortisol levels among patients with HF. Methods: A quasi-experiment was used in this study. A sample size of 18 respondents consists of 9 respondents of the control group and 9 respondents of the treatment group. Dhikr intervention was conducted in three meetings with an interval of two days during patients' hospitalization. Spirituality was measured using a spirituality questionnaire, whereas the cortisol levels with venous blood sampling, measured by the enzyme-linked fluorescent immunoassay (ELFA) method. Statistics analysis in this study was using t-Test for spirituality, Mann Whitney and Wilcoxon Sign Rank Test for cortisol level with a significance level of α<0.05. Results:  The results showed that dhikr improves the spirituality of HF patients (p=0.000) and decreases the level of cortisol (p=0.015) significantly. Dhikr interventions appears to strengthen spirituality in patients with HF by improving stress perception which further modulates the adaptive stress response in the form of decreasing cortisol levels. Conclusions: Dhikr could be one of the spiritual nursing interventions to improve spirituality and stress hormonal modulation in patients with HF.